Novos complexos de prata(I) com hidrazonas: atividades citotóxica e antimicrobiana e estudo de interações com alvos biológicos - Ane Francielly da Silva Santos (2018)
The therapeutic potential of silver(I) complexes with hydrazones has not been fully investigated. Hence, in the present work, silver(I) complexes were obtained with 2-acetylpyridine-2-benzoylpyridine and 2,6-diacetylpyridine-derived hydrazones aiming to develop new antifungal and antitumor silver-based drug candidates.Complexes [Ag(H2AcPh)NO3] (1), [Ag(H2AcpCH3Ph)NO3] (2), [Ag(H2AcpClPh)NO3] (3) and [Ag(H2AcpNO2Ph)NO3] (4) were obtained with 2-acetylpyridine benzoylhydrazone (H2AcPh) and its para-methyl- (H2AcpCH3Ph), para-chloro- (H2AcpClPh) e para-nitro (H2AcpNO2Ph)benzoylhydrazone derivatives. Complexes [Ag(H2BzPh)NO3] (5), [Ag(H2BzpCH3Ph)NO3] (6), [Ag(H2BzpClPh)NO3] (7) and [Ag(H2AcpNO2Ph)NO3] (8) were obtained as well with the 2-benzoylpyridine benzoylhydrazone analogues. Complexes (1-4) showed antifungal activity against Candida and filamentous fungal strains.Complex (2) revealed to be more active than nystatin against Aspergillus niger, Aspergillus parasiticus and Penicillium citrinum while (4) was as active as nystatin against P. citrinum. SAR studies suggested that in general the antifungal effects against Candida strains exhibited goodcorrelation with the HOMO energy, indicating that an external electrophilic attack to these compounds or a donation of electronic density from these compounds to the receptor might be involved in their mode of action. On the other hand, for Aspergillus and Penicillium strains theactivities correlate well with logP, suggesting that the ability of the compounds to cross the cell membrane might be responsible for their antimicrobial activity. The cytotoxic effects of the complexes (1-4) were evaluated against B16F10 melanoma cells and against Melan-A non-malignant melanocyte cells. In some cases upon coordination to silver(I) the cytotoxic activity and the selectivity indexes significantly increased. Complexes (1-3) revealed to be more cytotoxic than cisplatin on B16F10 cells. In addition, (2) showed higher selectivity againstB16F10 melanoma than against Melan-A non-malignant melanocyte cells. The crystal structures of complexes (5-7) show long Ag-O1(hydrazone) and Ag-O3(NO3-) bond distances, suggesting a weak interaction of these oxygen atoms with the silver(I) center. Theoreticalcalculations were in agreement with the crystallographic data. In addition, theoretical calculations revealed that the Ag-hydrazone bond distances increase with the decrease of the nitrate-silver(I) distances, indicating aa weakening of the Ag-hydrazone bonds. The theoretical study alsodemonstrated the predominantly electrostatic nature of the chemical bonds around the silver(I) center. Coordination to silver(I) in complexes (5-7) proved to be a good strategy for antifungal activity improvement, the best results being obtained for complex (7), which was as active as nystatin against Candida glabrata and 2-fold more active than nystatin against Penicillium citrinum. Complexes (5-7) revealed to be more cytotoxic than cisplatin on B16F10 melanoma cells andto be more cytotoxic against melanoma than against Melan-A non-malignant melanocyte cells. Complex (5) showed higher selectivity index (SI = 23) than the parent hydrazone H2BzPh (SI = 9.5),suggesting that complexation to silver(I) was a good strategy for increasing selectivity. A second family of silver(I) complexes, [Ag(H2-2,6AcPh)]NO3 (9), [Ag(H2-2,6AcpCH3Ph)]NO3 (10), [Ag(H2-2,6AcpClPh)]NO3·2H2O (11) and [Ag(H2-2,6AcpNO2Ph)]NO3(12) were obtained with 2,6-diacetylpyridine bis(benzoylhydrazone) (H2-2,6AcPh) and its bis(paramethyl-benzoylhydrazone) (H2-2,6AcpCH3Ph), bis(para-chloro-benzoylhydrazone) (H2-2,6AcpClPh) and bis(para-nitro-benzoylhydrazone) (H2-2,6AcpNO2Ph) derivatives. These compounds were designed to show structural characteristics suitable for their interaction with DNAby an intercalative mode. In some cases the antifungal activity increased upon coordination to silver(I) in complexes (9-12). Complex (10) was as active as miconazole nitrate against Candida albicans while (9) was more active than nystatin against Penicillium citrinium. In addition, both complexes were as potent as nystatin against Aspergillus parasiticus. Complex (10) showed selectivity for Candida albicans. Complexes (1-7) and (9-12) interact with human serum albumin (HSA) by a static suppresion mechanism. The thermodynamic parameters indicated that the interactions occur mainly via hydrogen bonding and/or van der Waals forces. Hence these complexes might be transported by HSA in theblood stream. The complexes also interact with DNA by an intercalative mode but covalent binding of silver(I) to DNA most probably does not occur. The binding constants for complexes (9-12) are higher than those of the remaining complexes, in according to their planar structures.Coordination of the hydrazones under study to silver(I) proved to be an interesting strategy for the development of new antimicrobial and anticancer metallodrug candidates. The present workconstitutes an important contribution to Medicinal Inorganic Chemistry.